Consideration of Digital Divide in Societies of Globalised Control (Extension of Social Contract) - Hüseyin Tolu (Türkiye İletişim Araştırmaları Dergisi)
If social cybernetics is clarified as an ‘emergent property’ for the multifaceted established of interior associations in the midst of technology, policy and management foundations of wide-ranging resolution computing, we should askare[MOK1]there any implementation of its definition in the sociology of technology? Therefore, this[MOK2]paper introduces multidimensional perspectives of techno-social interactions to diagram a theoretical concept of digital divide (DD) and elucidate its limitation stages within the relative literature. What the current reality is that we cannot escape from a global prison even if we do know we are in one, in this sense, this paper is interested in arguing how the definition of DD leads technocratic reasoning in which societies of globalised control cannot be separated from speculation, accumulation and circulation of technological commodities that actually lead an unspecific but an extension of social contract in any developed or developing nations throughout technological education.[A3]Political philosophy is then inseparable from ethnics of social cybernetics because the relative issue is rather assemblage of abstract technological control.Keywords:Cybernetics; Digital Divide; Sociology of Technology; Sociology of Education, Social Contract; Communication